The Effect of Chinese Medicinal Formulas on Biomarkers of Oxidative Stress in STZ-Induced Diabetic Kidney Disease Rats: A Meta-Analysis and Systematic Review - Zhou, Qian; Han, Chuyi; Wang, Yanmei; Fu, Shunlian; Chen, Yiding; Chen, Qiu (Frontiers in Medicine, 2022)
Background Diabetic kidney disease (DKD), defined broadly as persistent proteinuria with low estimated glomerular filtration rate in patients with diabetes, is a main cause of end-stage renal disease. Excessive production of reactive oxygen species is an important mechanism underlying the pathogenesis of diabetic nephropathy, and many antioxidants have been investigated as therapeutic agents. Among them, Chinese Medicine anti-oxidative stress therapies have been widely used to combat diabetic kidney disease which may offer new insights into therapeutic development of diabetic kidney disease. Methods We searched Pub Med, Cochrane Library, Web of Science databases and EMBASE from inception to December 2021 using relevant keywords and a comprehensive search for randomized controlled trials (RCTs) was performed. Calculating the pooled weighted mean difference (MD) and it 95% confidence interval (CI) by the method of inverse-variance with a random-effect. All related statistical analyses were performed using Stata V.15.1 software (Stata Corp) and Rvman 5.3 (Nordic Cochrane Center). Results 8 articles with 9 groups including 106 in the model group, 105 in Chinese Herbal Formulas (CHF) group and 99 in Western medicine group. Pooled data from 8 studies (9 groups) showed a statistical improve in superoxide dismutase compared with model group (SMD = 1.57; 95CI: 1.16 to 1.98; P < 0.05) and Western medicine group (SMD = 0.56; 95CI: 0.19 to 0.92; P < 0.05). For GSH-PX, significantly improved vs model group and Western medicine group. For MDA, significantly reduced in CHF group (CHF vs model group: SMD = -1.52; 95 CI: -1.88 to -1.17; P < 0.05; CHF vs Western medicine: SMD = -0.64; 95 CI: -0.95 to -0.33; P < 0.05). Conclusion This systematic review and meta-analysis have demonstrated that the therapy of CHF had a notable curative effect on relieving oxidative stress in diabetic kidney disease, and CHF was significantly more effective than Western medicine control group. For the clinical application, the results providing confidence and some theoretical reference for DKD via evaluating the efficacy of CHF to a certain extent.